Development of a comprehensive treatment algorithm for tandem spinal stenosis: decision making and surgical strategy - Kanna, Rishi M.; Iyer, Praveen R.; Shetty, Ajoy Prasad; Rajasekaran, Shanmuganathan (The spine journal, 2025)
Tandem spinal stenosis (TSS) can present with a constellation of myriad neurological symptoms and signs. Whole spine MRI has improved the diagnosis but does not aid therapeutic decision-making. While most studies have focused on cervico-lumbar TSS, there is inadequate literature on TSS of other regions. Further, there are no guidelines on the optimal surgical strategy for patients with TSS. Retrospective evaluation of prospectively collected data To develop a clinico-radiological treatment algorithm for TSS involving all the regions of the spine About 238 patients treated for TSS with a minimum follow-up of 2 year. The patients were classified based on the areas of stenosis namely cervico-lumbar (Type A -186), cervico-thoracic (Type B -11), thoracolumbar (Type C -24), and cervical, thoracic & lumbar (Type D -17). The criteria for diagnosis of TSS were cord compression and T2 signal intensity changes in cervical/ thoracic regions, and/or Schiza’s grade ≥C lumbar canal stenosis (LCS). In the sequence of surgical algorithm, clinical severity was taken as the prime factor followed by cord signal changes. In clinical severity, symptoms were given predominance over clinical signs, myelopathy over radiculopathy and proximal over distal compressions. The outcomes were evaluated through Nurick’s grade (NG) and ODI. Type A cervico-lumbar TSS was divided into four sub-types. Type A1-patients with clinical myelopathy without symptoms of LCS underwent cervical decompression alone (n=58). NG improved from 3.8±0.98 to 1.74±0.74 (p<.05). Only 11(18%) required lumbar decompression later. Patients with LCS (Type A2) without clinical myelopathy underwent lumbar decompression alone (n=97). Four (4.1%) developed myelopathy during follow-up requiring a cervical surgery. Patients with predominant LCS symptoms with only signs of myelopathy (Type A3, n=7) underwent lumbar decompression initially but all required cervical surgery within 2 years. Type A4 (n=24) with both myelopathy and claudication symptoms were treated by combined staged decompressions procedures. The NG improved from 3.4±0.7 to 1.6±0.4 (p<.05). Type B (n=11) had patients with myelopathy due to compression at cervical and thoracic regions. They were sub-divided based on upper limb myelopathy. In patients with both upper and lower limb myelopathy (Type B1, n=11), cervical decompression was done first (n=6) followed by staged thoracic decompression. The NG improved from 4.6±0.5 to 1.8±0.3 (p<.05). In patients with predominant lower limb myelopathy (Type B2, n=5), only thoracic surgery was performed. Only one required cervical surgery later. In Type C thoracic & lumbar TSS (n=24), 20 were treated by thoracic decompression based on signs of myelopathy. The mean NG improved from 4.1±0.7 to 1.9±0.9 (p<.05). Six cases required lumbar level surgery later. Four patients who had only LCS symptoms underwent lumbar decompression. Type D with stenosis at all three regions presented variedly, and underwent staged decompression (n=17). Based on clinical features of myelopathy and claudication, along with specific diagnostic MRI criteria, the present study comprehensively classified all possible types of TSS. The algorithm provides specific surgical strategies for each subtype, based on a large cohort of patients. More than MRI evidence of stenosis and signal changes, clinical symptoms and signs were helpful in formulating treatment.